"Do I fit in?" Signals on corporate websites. Issue 7 (12th October 2018) - Stockdale, Emma; William, Laura Catherine; Arevshatian, Lilith
Abstract : Purpose: Prospective job applicants tend to use signals that are presented on corporate websites to form perceptions about the organizations. Specifically, they decide whether they would "fit in." The purpose of this paper is to examine the explicit and implicit signals presented by Financial Times Stock Exchange 250 Index (FTSE250) companies on their corporate websites. Design/methodology/approach: A content analysis was carried out on FTSE250 corporate websites. Findings: While many corporate websites do include general references to diversity, they do not engage with different protected characteristics on an equal basis. Furthermore, corporate websites often espouse the legal and business cases rationale for engaging with diversity. Research limitations/implications: The authors were restricted by the information presented on corporate websites. Further research could use a multi-modal approach and include analysis of images. Practical implications: Companies need to consider their overall rationale for engaging with diversity. Fostering a culture of inclusion where diversity is celebrated will allow companies to showcase their genuine commitment to diversity on their websites and avoid sending disingenuous signals to minority groups. Social implications: Increasing the perceived "fit" of minority groups in an organizational culture will foster inclusion and diversity and support minority group engagement. Originality/value: This research examines diversity signals and relates these to job applicants' perceptions.